Eye-Light on Age-Related Macular Degeneration: Targeting Nrf2-Pathway as a Novel Therapeutic Strategy for Retinal Pigment Epithelium - Catanzaro, Michele; Lanni, Cristina; Basagni, Filippo; Rosini, Michela; Govoni, Stefano; Amadio, Marialaura (Frontiers in Pharmacology, 2020)
Age-related macular degeneration (AMD) is a common disease with a multifactorial aetiology, still lacking of effective and curative therapies. Among the early events triggering AMD is the deterioration of the retinal pigment epithelium (RPE), whose fundamental functions assure good health of the retina. RPE is physiologically exposed to high levels of oxidative stress during its life-span; thus, the integrity and well-functioning of its antioxidant systems are crucial to maintain RPE homeostasis. Among these defensive systems, the Nrf2-pathway plays a primary role. Literature evidence suggests that, in aged and especially in AMD RPE, there is an imbalance between the increased pro-oxidant stress, and the impaired endogenous detoxifying systems, finally reverberating on RPE functions and survival. In this in vitro study on wild type (WT) and Nrf2-silenced (siNrf2) ARPE-19 cells exposed to various AMD-related noxae (H2O2, 4-HNE, MG132+Bafilomycin), we show that the Nrf2-pathway activation is a physiological protective stress response, leading down-stream to an up-regulation of the Nrf2-targets HO1 and p62, and that a Nrf2 impairment predisposes the cells to a higher vulnerability to stress. In search of new pharmacologically active compounds potentially useful for AMD, four nature-inspired hybrids (NIH) were individually characterized as Nrf2 activators, and their pharmacological activity was investigated in ARPE-19 cells. The Nrf2 activator dimethyl-fumarate (DMF; 10 μM) was used as a positive control. Three out of the four tested NIH (5 μM) display both direct and indirect antioxidant properties, in addition to cytoprotective effects in ARPE-19 cells under pro-oxidant stimuli. The observed pro-survival effects require the presence of Nrf2, with the exception of the lead compound NIH1, able to exert a still significant, albeit lower, protection even in siNrf2 cells, supporting the concept of the existence of both Nrf2-dependent and independent pathways mediating pro-survival effects. In conclusion, by using some pharmacological tools as well as a reference compound, we dissected the role of the Nrf2-pathway in ARPE-19 stress response, suggesting that the Nrf2 induction represents an efficient defensive strategy to prevent the stress-induced damage.